Should patients on levothyroxine therapy be screened for pancreatic cancer? Pancreatic cancer and hypothyroidism - Garajova, Ingrid; Balsano, Rita; Coriano', Matilde; Gelsomino, Fabio; Tovoli, Francesco; De Lorenzo, Stefania; Del Rio, Paolo; Dalla Valle, Raffaele; Ravaioli, Matteo; Leonardi, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Background: Pancreatic ductal adenocarcinoma is an aggressive disease with increasing incidence. Thyroid hormones play different roles in development and physiological processes of the entire digestive system, including pancreas. Therefore, many have hypothesized that thyroid hormone supplementation for hypothyroidism disorders might increase the risk of malignancy. Patients and methods: We conducted retrospective observational mono-centre study. The aim was to examine the prevalence of thyroid disorders among patients with pancreatic cancer. Moreover, we investigated the impact of thyroid hormone supplementation in pancreatic cancer patients’ outcome and the correlation with various clinicopathologic parameters. Results: A total of 92 consecutive pancreatic cancer patients were retrospectively reviewed: 18.5% patients had a history of hypothyroidism and all received a replacement hormone therapy with levothyroxine, in particular 20% in metastatic group and 11% in radically resected PDAC patients’ group. Nor in radically resected neither in metastatic group, we did not observe any statistically significant difference in outcome between the group with or without thyroid disorders. On multivariate analyses, cox proportional hazards model analysis showed that only the presence of perineural invasion was associated with a significantly higher hazard ratio for overall survival in metastatic PDAC patients (HR=2.7; 95%CI=1.029-6.925; p=0.009). Conclusions: We observed higher prevalence of thyroid disorders in PDAC patients. Further studies are warranted to explore the impact of levothyroxine therapy on outcome in PDAC patients.